GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 58 species occurrences available in GBIF matching the query: TaxonKey: Opuntia tunicata (Lehm.) Pfeiff.. The dataset includes 58 records from 11 constituent datasets: 4 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from ICN - Universidad Nacional de Colombia. 30 records from Tropicos Specimen Data. 1 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 2 records from Repatriación de datos del Herbario de Arizona (ARIZ). 1 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 7 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from Instituto de Ciencias Naturales. 1 records from Instituto de Botánica Darwinion. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences